Utilización de materiales didácticos para desarrollar la noción de cantidad en niños de primer grado EGB de la UE. Eloy Alfaro Delgado Guamote, Guamote, Chimborazo. - Mullo Mullo, Segundo Pablo (2023)
Within the development of logical-mathematical relationships of children in the first year of primary education, it is essential to establish the comparison of notions of quantity such as a lot, a little, one, nothing. That is why the research aimed to develop a proposal for teaching material to create quantity in first-grade children of Basic General Education in the EU. Eloy Alfaro Delgado. Methodologically, a qualitative approach was used, with a bibliographic design, systematic review, descriptive, transversal, and propositional level. The technique used was observation, and the instrument was registering bibliographic records. To analyze the information, a search strategy was developed in the following digital platforms: SciELO, Dialnet, Redalyc, Academia, ResearchGate, Google Academic, and repositories of different universities. The descriptors used were Teaching material, development of teaching guides, teaching and learning of mathematics in preparatory education, logical-mathematical relationships, and quantity notion. Subsequently, search chains were created to determine the selected articles. Thus, 68 investigations were obtained, where the inclusion and exclusion criteria were applied, leaving 21 documents that meet the proposed objectives. Conclusion: The use of teaching materials in mathematics facilitates students' understanding and communication, as it favors attention and concentration. The development of the notion of quantity functions as a mediator of learning, allowing the development of logical-mathematical thinking; children must be allowed to manipulate the material freely and simultaneously guide them. High school teachers should use teaching materials according to their environment to facilitate learning.